KAJIAN PERTUNJUKAN MUSIK IRINGAN TARI JOGI DI SANGGAR WARISAN PANTAI BASRI PULAU PANJANG BATAM KEPULAUAN RIAU - Joel Franky Situmeang; Agusti Efi (Fakultas Bahasa dan Seni Universitas Negeri Medan, 2023)
This research is a case study of musical performance in the Basri Heritage Beach Group or SWPB. Where SWPB always promotes and performs Jogi music. Jogi is a music and dance performance that tells the story of a wife who is left by her husband when she goes to sea. The form of a musical performance entitled